Reliability and validity of the electronic version of the Hopkins verbal learning test-revised in middle-aged and elderly Chinese people - Jiang, Lichen; Xu, Ming; Xia, Shunyao; Zhu, Jiahui; Zhou, Qi; Xu, Luoyi; Shi, Chuan; Wu, Daxing (Frontiers in Aging Neuroscience, 2023)
Background The aging population is increasing, making it essential to have a standardized, convenient, and valid electronic memory test that can be accessed online for older people and caregivers. The electronic version of the Hopkins Verbal Learning Test-Revised (HVLT-R) as a test with these advantages and its reliability and validity has not yet been tested. Thus, this study examined the reliability and validity of the electronic version of the HVLT-R in middle-aged and elderly Chinese people to provide a scientific basis for its future dissemination and use. Methods We included 1,925 healthy participants aged over 40, among whom 38 were retested after 3–6 months. In addition, 65 participants completed both the pad and paper-and-pencil versions of the HVLT-R (PAP-HVLT-R). We also recruited 42 Alzheimer’s disease (AD) patients, and 45 amnestic mild cognitive impairment (aMCI) patients. All participants completed the Pad-HVLT-R, the Hong Kong Brief Cognitive Test (HKBC), the Brief Visual Memory Test-Revised (BVMT-R), and the Logical Memory Test (LM). Results (1) Reliability: the Cronbach’s α value was 0.94, the split-half reliability was 0.96. The test–retest correlation coefficients were moderate, ranging from 0.38 to 0.65 for direct variables and 0.16 to 0.52 for derived variables; (2) Concurrent validity: the Pad-HVLT-R showed a moderate correlation with the HKBC and BVMT-R, with correlation coefficients between total recall of 0.41 and 0.54, and between long-delayed recall of 0.42 and 0.59, respectively. It also showed a high correlation with the LM, with correlation coefficients of 0.72 for total recall and 0.62 for long-delayed recall; (3) Convergent validity: the Pad-HVLT-R was moderately correlated with the PAP version, with correlation coefficients ranging from 0.29 to 0.53 for direct variables and 0.15 to 0.43 for derived variables; (4) Discriminant capacity: the Pad-HVLT-R was effective in differentiating AD patients, as demonstrated by the ROC analysis with AUC values of 0.834 and 0.934 for total recall and long-delayed recall, respectively. Conclusion (1) The electronic version of HVLT-R has good reliability and validity in middle-aged and elderly Chinese people; (2) The electronic version of HVLT-R can be used as an effective tool to distinguish AD patients from healthy people.